2020
DOI: 10.4103/sjg.sjg_58_20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single- versus split-dose polyethylene glycol electrolyte solution for morning colonoscopy: A randomized controlled study

Abstract: Background: Split-dose (SPD) regimen has been proved more effective than a single-dose (SID) regimen for various drug preparations; however, limited data have focused on morning colonoscopy. We implemented this study to compare the bowel cleanliness and tolerability of a same-day SID versus SPD 2 L polyethylene glycol electrolyte solution (PEG) for morning colonoscopy. Methods: Patients undergoing morning colonoscopy were randomized into two groups, SID or SPD. In the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Similarly, Shan et al [30], in a randomized controlled trial on 295 patients, demonstrated that for morning colonoscopy, split-dose 2L PEG was superior to single-dose regimen in bowel preparation and patients tolerability and satisfaction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Shan et al [30], in a randomized controlled trial on 295 patients, demonstrated that for morning colonoscopy, split-dose 2L PEG was superior to single-dose regimen in bowel preparation and patients tolerability and satisfaction.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding procedure related risk factors, several studies have proposed that low-volume hyperosmolar PEG and split-dose regimen were associated with an higher rate of adequate bowel cleansing [25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the complete bowel‐cleansing preparation is administered in the evening before the colonoscopy. And, to avoid sleep disruption, it must be administered early in the evening, resulting in poor bowel cleansing reported as a 70% sufficient cleaning rate, 42 which was much lower in our center at 50% because we only utilized low‐volume 2 L PEG. The main cause of poor bowel cleanliness could be the long‐time interval between the last preparation intake and the time of the colonoscopy, which was supposed to be limited to 4–6 h. To meet the recommended interval time for the morning colonoscopy, patients had to get up at dawn.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Separate 2 + 2L bowel preparation was superior to one-time 4 L (89.2% vs 62.5%; P < .001). [8] 2. Materials and Methods…”
Section: Introductionmentioning
confidence: 88%
“…[7] Separate-time bowel preparation quality was better than one-time bowel preparation, with an overall BBPS score of 7.25 ± 1.53 vs 6.71 ± 1.65 ( P = .005). [8] Separate 2 + 2L bowel preparation was superior to one-time 4 L (89.2% vs 62.5%; P < .001). [8]…”
Section: Introductionmentioning
confidence: 99%